Lethal diquat poisoning manifesting as central pontine myelinolysis and acute kidney injury: A case report and literature review. Issue 7 (July 2020) - Xing, Jihong; Chu, Zhe; Han, Dongfeng; Jiang, Xiaoming; Zang, Xiuxian; Liu, Yajie; Gao, Song; Sun, Lichao
Diquat is a nonselective herbicide that is used as a contact and preharvest desiccant to control terrestrial and aquatic vegetation. Increasing numbers of cases of diquat poisoning have recently been reported. Organs commonly affected by diquat poisoning include the kidney, liver, and lung. Neurological involvement of diquat poisoning is relatively rare. A 21-year-old man ingested 100 mL of diquat (20 g/100 mL) 5 hours before admission. Fifteen minutes after ingestion, he developed nausea and vomiting. The patient was sent to the emergency intensive care unit, and gastric lavage was performed. Continuous renal replacement therapy and continuous venovenous hemodiafiltration with hemoperfusion were performed, and methylprednisolone was administered. Five days after admission, the patient developed disturbance of consciousness and positive bilateral Babinski signs. Head computed tomography demonstrated hypodensity in the pons. At 11 days after admission, brain magnetic resonance imaging showed acute pontine demyelination. At 15 days after admission, the patient died of multiple organ dysfunction syndrome. We encountered a case of diquat poisoning with central pontine myelinolysis and acute kidney injury. This case highlights the clinical value of neuroimaging examination for early diagnosis of central pontine myelinolysis.